Storytelling, Safeguarding, Treatment, and Responsibility: attributes of recovery in psychiatric intensive care units. (19th December 2014) - Gwinner, Karleen; Ward, Louise
Abstract: Background and aim: In recent years, policy in Australia has endorsed recovery-oriented mental health services underpinned by the needs, rights and values of people with lived experience of mental illness. This paper critically reviews the idea of recovery as understood by nurses at the frontline of services for people experiencing acute psychiatric distress. Method: Data gathered from focus groups held with nurses from two hospitals were used to ascertain their use of terminology, understanding of attributes and current practices that support recovery for people experiencing acute psychiatric distress. A review of literature further examined current nurse-based evidence and nurse knowledge of recovery approaches specific to psychiatric intensive care settings. Results: Four defining attributes of recovery based on nurses' perspectives are shared to identify and describe strategies that may help underpin recovery specific to psychiatric intensive care settings. Conclusion: The four attributes described in this paper provide a pragmatic framework with which nurses can reinforce their clinical decision-making and negotiate the dynamic and often incongruous challenges they experience to embed recovery-oriented culture in acute psychiatric settings.